On Ï†ÏÏƒÎ¹Ï‚. What did the Greeks understand by Ï†Ï…ÏƒÎ¹ÎºÏŒÏ‚? - Bernabe, Alberto (Revista Archai, 2017)
The uses of Ï†Ï…ÏƒÎ¹ÎºÏŒÏ‚ from its former occurrences until the III BC. are examined. After an analysis of the first instances of the term, its uses may be classified into two large groups. In the former, Ï†Ï…ÏƒÎ¹ÎºÏŒÏ‚ can be understood as “natural” or “innate” and various sections can be identified: a) applied to objects or beings, as opposed to ‘artificial’, b) to refer to “natural structures”, c) to qualify properties in the ‘inherent’ sense, d) to attribute to productions and effects of natural activity, in the sense that nature is an active and conscious principle, e) to define capacities, abilities or instincts as opposites to ‘learned’, f) to distinguish activities, behaviours and relationships which they are the result of the customs, g) to apply to laws and justice, as opposed to ‘conventional’, h) with the idea of ‘appropriate’, ‘characteristic’ and (i) opposed to ‘psychic’. The second group includes the uses in which Ï†Ï…ÏƒÎ¹ÎºÏŒÏ‚ is understood as ‘referring to nature as object of study’